2013
DOI: 10.2174/1567205011310020005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SORL1 Gene on Alzheimer's Disease. Focus on Gender, Neuropsychiatric Symptoms and Pro-Inflammatory Cytokines

Abstract: It was suggested that the gene encoding for sorLa, (SORL1) may affect Alzheimer's disease (LOAD) through a female-specific mechanism. The aims of this study were to confirm the role of gender in modulating the association between SORL1 and LOAD and to ascertain the influence of SORL1 on cognitive impairment, neuropsychiatric symptoms (BPSD) and secretion of pro-inflammatory cytokines. Ninety six outpatients with LOAD and 120 unrelated controls were genotyped for APOE and three SNPs at the 5' end of SORL1(intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Cellini et al reported an association between SORL1 rs661057 polymorphism and LOAD in women but not in men [49]. We also confirmed the association between SORL1 SNPs and LOAD in a subgroup of women from the GIGAS_LOAD sample [25]. When looking at gene-gene interactions, SORL1 variants have been associated with AD in non-carriers of the APOE epsilon 4 allele but not in its carriers [49; 50].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Cellini et al reported an association between SORL1 rs661057 polymorphism and LOAD in women but not in men [49]. We also confirmed the association between SORL1 SNPs and LOAD in a subgroup of women from the GIGAS_LOAD sample [25]. When looking at gene-gene interactions, SORL1 variants have been associated with AD in non-carriers of the APOE epsilon 4 allele but not in its carriers [49; 50].…”
Section: Discussionsupporting
confidence: 82%
“…Inflammatory process might enhance neurodegeneration. In fact we could observe higher levels of pro-inflammatory intrleukin 1-beta in AD patients with TAT haplotype [25].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations